Synthesis of Nitroxide-Annulated Carbocycles and Heterocycles - Kálai, Tamás; Bognár, Balázs; Zsolnai, Dániel; Berente, Zoltán; Hideg, Kálmán (Synthesis, 2012)
New, pyrroline nitroxide annulated lactones, polycycles, and maleimide were synthesized by classical and microwave-assisted methodology. We report the application of the metathesis reaction in the presence of nitroxide yielding a pyrroline nitroxide condensed 1,4-benzoquinone as a paramagnetic dienophile. The formation of the isoselenazolone-fused pyrroline ring system was examined and different reactivity was observed with pyrrolin-1-oxyl and pyrroline derivatives.
Keywords: free radicals; heterocycles; lactones; metathesis; quinones